K-bentonite, black-shale and flysch successions at the Ordovician–Silurian transition, South China: Possible sedimentary responses to the accretion of Cathaysia to the Yangtze Block and its implications for the evolution of Gondwana - Su, Wenbo; Huff, Warren D.; Ettensohn, Frank R.; Liu, Xiaoming; Zhang, Ji'en; Li, Zhiming (Gondwana research, 2009)
The K-bentonite, black shale and flysch successions at the Ordovician–Silurian transition in South China have been the subject of comprehensive investigations relative to the probable accretion of the Yangtze Block and the questionable Cathaysia Block. First, the geochemical analyses of K-bentonites show that the parent magma originated in syn-collisional, volcanic-arc and within-plate tectonic settings, which produced mainly intermediate-to-felsic series magmas, associated with continuous collision and subduction of paleo-continental blocks/arcs. Further, the regional distribution of K-bentonite thickness indicates that voluminous explosive volcanism was located in the present southeastern shoreline provinces of China. Secondly, northwestwardly migrating, Ordovician–Silurian, transitional flysch successions, and the accompanying diachronous K-bentonite-bearing black-shale interval, as well as the related, overlying, shallowing-upward succession at the interior of the Yangtze Block, developed as an unconformity-bound sequence that mirrors foreland-basin tectophase cycles in the Appalachian basin. The above features suggest that the sequence accumulated in a similar foreland basin, which formed in response to adjacent deformational loading in a northwesterly migrating orogen located to the southeast. Geochemical and paleocurrent data from the turbiditic flyschoid sandstones also support these depositional settings. Accordingly, it seems that all criteria strongly support the presence of an Ordovician–Silurian, subduction-related orogen resulting from collision with a block to the southeast that must have been the original “Cathaysia Block” of Grabau and later workers. The K-bentonite, black-shale and flysch successions can be regarded as distal, foreland responses to the continuous northwestward collision and accretion of the Cathaysia Block to the Yangtze Block. Hence, we prefer to suggest that the suture zone with the sensu stricto Cathaysia Block probably developed along previously identified late Early Paleozoic suture relicts in the shoreline provinces of southeast China. On the other hand, although accretion of fragments with Cathaysian affinities to the Yangtze Block may have begun as early as Middle to Late Proterozoic time, the Ordovician–Silurian orogeny described above probably reflects the final phase of accretion between the two blocks. Moreover, when combined with similar peri-Iapetan orogenic events in other areas during the same period, this accretion event may have been part of a major stage of global tectonic reconstruction in the evolution of Gondwana.